Factors influencing mortality in COVID-19-associated mucormycosis: The international ID-IRI study - Sahin, Meyha; Yilmaz, Mesut; Mert, Ali; Naghili, Behrouz; Ravanbakhsh, Fatemeh; Varshochi, Mojtaba; Erdem, Hakan (Oxford Univ Press, 2024)
The emergence of COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), triggered a global pandemic. Concurrently, reports of mucormycosis cases surged, particularly during the second wave in India. This study aims to investigate mortality factors in COVID-19-associated mucormycosis (CAM) cases, exploring clinical, demographic, and therapeutic variables across mostly Asian and partly African countries. A retrospective, cross-sectional analysis of CAM patients from 22 medical centers across eight countries was conducted, focusing on the first 3 months post-COVID-19 diagnosis. Data collected through the ID-IRI included demographics, comorbidities, treatments, and outcomes. A total of 162 CAM patients were included. The mean age was 54.29 +/- 13.04 years, with 54% male. Diabetes mellitus (85%) was prevalent, and 91% had rhino-orbital-cerebral mucormycosis. Surgical debridement was performed in 84% of the cases. Mortality was 39%, with advanced age (hazard ratio [HR] = 1.06, [P < .001]), rituximab use (HR = 21.2, P = .05), and diabetic ketoacidosis (HR = 3.58, P = .009) identified as risk factors. The mortality risk increases by approximately 5.6% for each additional year of age. Surgical debridement based on organ involvement correlated with higher survival (HR = 8.81, P < .001). The utilization of rituximab and diabetic ketoacidosis, along with advancing age, has been associated with an increased risk of mortality in CAM patients. A combination of antifungal treatment and surgical intervention has demonstrated a substantial improvement in survival outcomes.
Keywords: COVID-19; COVID-19-associated mucormycosis; immunosuppression; mortality